Mechanical Properties And Bioactivity Of Ti-Nb-Ha Composite Fabricated By Mechanical Alloying - Ahmad, Farrah Noor (2020)
Titanium is the most popular metallic biomaterial for orthopaedic implant owing to their excellent mechanical properties and good corrosion resistance. However, the mismatch of elastic modulus and poor bonding with bones due to its bioinert behaviour has been identified as the major reason that lead to the implant loosening and eventual failure of the implantation. The present work investigates the mechanical performances and bioactivity of titanium-niobium-hydroxyapatite (Ti-Nb-HA) composite prepared by mechanical alloying and powder metallurgy. To study effect of HA and Nb , HA and Nb were varied from 0 to 15 wt.% and 0 to 40 wt.%, respectively. The powders of Ti, Nb and HA were mixed in a high energy ball mill for 2 hours at 200 rpm and followed by compaction under 500 MPa and sintering at 1200°C. Due to the brittleness of HA, the incorporation of HA decreased the compressive strength (1001.24 MPa to 160.94 MPa) and microhardness (300.53 HV to 85.47 HV). Adding HA contribute to the poor bonding with matrix which is more pronounced to reduce the elastic modulus from 65.10 GPa to 29.91 GPa. With the increasing in HA content, the composite displayed good bioactivity characteristics evaluation in HBSS for 30 days. The highest bioactivity was exhibited by composite with 15 wt.% HA due to the highest apatite (3.40%). Factor affecting the bioactivity are believed to be caused by HA decomposition during sintering process that produces CaO and CaTiO3. As a result, the presence of these Ca2+ ions increased the calcium concentration and accelerated the apatite growth. Higher Nb content improved the compressive strength (199.95 MPa to 300.11 MPa) and microhardness (120.97 HV to 269.90 HV) due to solid solution strengthening. However, the presence of TiO2 and Ti2P decrease compressive strength with 40 wt.% Nb. Apart from that, the elastic modulus was slightly decreased with the rise of Nb content. The highest amount of β phase is obtained by 30 wt.% Nb (76%). Increasing in Nb content to 40 wt.% decreases elastic modulus owing to decrement in β phase as a consequence of HA decomposition that lead to the formation of TiO2 and Ti2P. The presence of β phase, high solubility of Ti2P and functional groups of OH- act as favourable site for apatite growth in composite consisting different amount of Nb. Upon immersion test in HBSS for 30 days, the highest bioactivity was attained by 30 wt.% Nb and followed by 40 wt.% Nb, 20 wt.% Nb, 10 wt.%. The enhanced of apatite growth in 40 wt.% Nb was found to be caused by the presence of biocompatibility phases of TiO2 and Ti2P. Composite with addition of 10 wt.% HA and 30 wt.% Nb displayed the best properties and holds great potential in providing mechanical support and bioactivity enhancement in getting similar cortical bone characteristics.